2022
DOI: 10.3390/ma15134696
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Temperatures on the Performance of Carbon Fiber Reinforced Polymer (CFRP) Composite Cables Protected with Fire-Retardant Materials

Abstract: In this study, the safe critical temperature that can be tolerated by CFRP tendons under normal working conditions was derived through tensile tests at room and high temperatures. Next, the times required to reach a safe critical temperature for CFRP cables protected with different types of fire-retardant materials of various thicknesses were determined through fire resistance tests, Finally, fitting the surface of the finite element simulation results allowed the establishment of the temperature rise calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In the study conducted by Zhuge et al [41], they conducted fire resistance tests to investigate the effect of two different fire-retardant materials, high-silica needled felt and ceramic fiber felt, on the fire resistance of CFRP tendons. Their criteria for evaluating fire resistance were based on a reduction in tensile strength and elastic modulus to 80% of their initial properties at 300 • C. In another study conducted by Khaneghahi et al [30], the results revealed that the flexural modulus retention of the composite was stable, staying above 90% of the initial performance after cooling from temperatures below 300-350 • C. Once exceeding the temperature of degradation, there was a rapid loss of flexural modulus retention.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…In the study conducted by Zhuge et al [41], they conducted fire resistance tests to investigate the effect of two different fire-retardant materials, high-silica needled felt and ceramic fiber felt, on the fire resistance of CFRP tendons. Their criteria for evaluating fire resistance were based on a reduction in tensile strength and elastic modulus to 80% of their initial properties at 300 • C. In another study conducted by Khaneghahi et al [30], the results revealed that the flexural modulus retention of the composite was stable, staying above 90% of the initial performance after cooling from temperatures below 300-350 • C. Once exceeding the temperature of degradation, there was a rapid loss of flexural modulus retention.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…Of various FRP composites, carbon fiber-reinforced polymer (CFRP) possesses the best resistance to creep, namely, it can sustain around 80% of the tensile strength without experiencing creep rupture [ 9 , 10 ]. Therefore, CFRP is recognized to be ideal for prestressing applications [ 11 , 12 , 13 ]. This non-corrosive composite material is particularly suitable for external tendons in lieu of conventional prestressing steel in overcoming the corrosive problem [ 14 , 15 ], as these tendons are exposed to harsh conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Fiber reinforced polymer (FRP) composites are recognized as a promising alternative to steel reinforcement in reinforced [ 19 , 20 , 21 , 22 ] and prestressed concrete applications [ 23 , 24 , 25 , 26 ]. This composite reinforcement may be made of carbon FRP (CFRP) [ 27 ], aramid FRP (AFRP) [ 28 ] or glass FRP (GFRP) [ 29 ].…”
Section: Introductionmentioning
confidence: 99%